Cytotoxic activity and phytochemical composition of Stereospermum binhchauensis V.S. Dang leaves. Issue 4 (16th February 2021) - Tri Mai, Dinh; Nghia Ngo, Trong; Ly Nguyen, Ngoc Thien; Luan Ngo, Quoc; Minh, Nhat Phan; Dat Bui, Trong; Dang, Van Son; Tran, Cong Luan; Tuyen Pham, Nguyen Kim; An Tran, Nguyen Minh; Nguyen, Tan Phat
Abstract: For the first time, the cytotoxic and phytochemical investigation of the leaves of Stereospermum binhchauensis V.S. Dang, a new species discovered in Viet Nam were finalized and led to purify nine compounds, including one furancoumarin (1), one chromone (3), two triterpenoids (2, 4), two flavonoids (5, 8), two flavanoids (6, 7) and one iridoid (9) using various chromatography methods. Their structures were verified by HR-ESI-MS, NMR experiments and compared with previous literatures. For the first time, compounds (5 –8) were realized from the genus Stereospermum, while compounds (1, 2, 3, 4 & 9 ) were designated from the species S. binhchauensis . Furthermore, the furancoumarin, chromone and flavanoid classes were notified for the first time from the genus Stereospermum. Graphical Abstract: